A performance analysis approach based on the UML class diagram. - Alsaadi, Ahmad (Software engineering notes.)
A data model, or UML class diagram of a software system, is of central importance to the computing time and the disk usage a software system exhibits. It can be normalized or denormalized to better utilize the components of a computer system or to offer acceptable performance values.This paper describes an approach to software performance analysis that is based on the UML class diagram. It predicts the performance values for use cases operating on persistent data collections as well as whether and how much normalization or denormalization a UML class diagram may need, in order to ensure that these use cases meet their performance objectives.